Risk, Efficiency and Return of PSBs in India (Global Journal of Management and Business Research, 2013)
The present study is an attempt to evaluate the performance of public sector banks in terms of credit risk, efficiency and their impact on the profitability of these banks. The study covered the period from 2000 to 2010. With the help of panel data regression analysis the study concludes that NPLs affect adversely the profitability of banks while risk aversion seems to be in favor of the public sector banks in India. Though significant progress has been made in NPLs management, much still need to be done in order to improve the performance of scheduled commercial banks. Keeping in view the gravity of credit risk, the study recommends steps, towards the recovery of such loans, to be undertaken and enforced by the RBI.
Keywords: NPLs; roa; panel data regression; banks